An unusual presentation of coexisting parathyroid carcinoma and papillary carcinoma thyroid: a case report and literature review - Puthen Veetil, Pradeep; Puzhakkal, Shikhil; Narayanan, Niya; Chakko, Anju (International Surgery Journal, 2023)
Parathyroid carcinoma is the rarest endocrine cancer with aggressive behaviour. It may be presented as a feature of severe hypercalcemia, musculoskeletal involvement and a neck mass. There should be a high clinical suspicion if there is marked hypercalcemia, very high parathyroid hormone levels, palpable neck mass, recurrent laryngeal nerve palsy due to invasion and severe bone and renal symptoms. Thyroid pathology has been seen in 15-70% of patients with primary hyperparathyroidism (PHPT) especially with parathyroid adenoma. Medullary thyroid carcinoma is common with PHPT as in MEN 2 syndrome and rarely co-existed with non-medullary thyroid carcinoma. Parathyroid carcinoma and papillary thyroid carcinoma is extremely rare. Only 16 cases are reported in the literature.